Polyester film and packaging bag using same

The development of a polyester film with specific viscoelastic and sealing properties addresses the issues of breakage and fragrance retention in packaging bags, providing enhanced performance for bags containing liquids.

JP7662979B2Active Publication Date: 2025-04-16TOYOBO CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2020074693
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-04-20
Publication Date
2025-04-16
Estimated Expiration
2040-04-20

AI Technical Summary

Technical Problem

Packaging bags made from polyester resin films suffer from breakage when liquid is placed in them, due to insufficient melting seal strength and fragrant retention properties.

Method used

A polyester film with specific properties, including a loss tangent (tanδ) between 0.03 and 0.15, a melting seal strength of 5N/15mm to 20N/15mm, and a glass transition temperature (Tg) between -75°C and 25°C, is developed. This film is designed to retain fragrances and maintain structural integrity when exposed to liquids.

Benefits of technology

The polyester film achieves excellent aroma retention, high melting seal strength, and enhanced breakage resistance when used in packaging bags containing liquids, making it suitable for various packaging applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007662979000005
    Figure 0007662979000005
  • Figure 0007662979000001
    Figure 0007662979000001
  • Figure 0007662979000002
    Figure 0007662979000002
Patent Text Reader

Abstract

To provide a polyester-based film that has aroma retention capability against various organic compounds, a high fusion seal strength, and a good bag-tear resistance when a liquid is put into the content as a packaging bag.SOLUTION: A polyester-based film satisfies the following requirements (1) and (2). (1) Loss tangent (tan δ) obtained when dynamic viscoelasticity is measured at 25°C is 0.03 or more and 0.15 or less in the longitudinal direction. (2) Fusion seal strength when fusing and sealing so that the width direction is the sealing direction is 5 N / 15 mm or more and 20 N / 15 mm or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyester film having excellent suitability for welding and sealing, and a packaging bag using the same. [Background technology]

[0002] Films are used as materials for bags that package various items such as food, medicine, and industrial products. Packaging bags are sometimes made by heat-cutting and sealing. Therefore, when selecting packaging materials, not only mechanical strength and transparency but also the strength and appearance of the heat-cut and sealed parts are taken into consideration. Films made of polyolefin resins are highly versatile due to these characteristics and are widely used as packaging materials. However, films made of polypropylene resins such as those described in Patent Document 1, for example, do not have sufficient odor prevention (aroma retention), so if the contents have a strong odor, the odorous components will pass through the film and leak out. On the other hand, packaging bags made of a film made of polyester resin as described in Patent Document 2 are less likely to adsorb organic compounds contained in chemical products, pharmaceuticals, food, etc., and are also less likely to allow odorous components to penetrate, so they have excellent aroma retention properties. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent No. 4867857 [Patent Document 2] JP 2017-210541 A [Non-patent literature]

[0004] [Non-Patent Document 1] Matsuo, M., Ueda, A., Kondo, Y.. Study on the fracture process of two-component polymers of resin and rubber. Polymer Chemistry. 1967, vol.24, no.264, p. 285-295. Summary of the Invention [Problem to be solved by the invention]

[0005] However, packaging bags that are heat-sealed using a film made of polyester resin as described in Patent Document 2 have a problem in that when liquid is poured into the contents, the bag breaks at the heat-sealed portion when the bag falls. In light of this situation, there has been a demand for a material that has high aroma retention and heat-seal strength for the contents, as well as good resistance to bag breakage when liquid is poured into the contents.

[0006] The present invention has been made in view of the above-mentioned circumstances, and an object of the present invention is to provide a polyester film that has aroma retention properties for various organic compounds, high heat-seal strength, and good resistance to tearing when used as a packaging bag to contain a liquid. Another object of the present invention is to provide a laminate including at least one layer of the polyester film, and a packaging bag using the laminate. [Means for solving the problem]

[0007] That is, the present invention comprises the following: 1. A polyester film that satisfies the following requirements (1) and (2): (1) The loss tangent (tan δ) obtained when measuring dynamic viscoelasticity at 25°C is 0.03 or more and 0.15 or less in the longitudinal direction. (2) When the film is welded and sealed in the width direction, the strength of the weld seal is 5N / 15mm or more and 20N / 15mm or less. 2. The polyester film according to claim 1, characterized in that the Tg measured by temperature modulated DSC is from -75°C to 25°C. 3. The polyester film according to claim 1 or 2, characterized in that the folding angle is 20 degrees or more and 80 degrees or less. 4. The polyester film according to any one of claims 1 to 3, characterized in that the heat shrinkage rate when immersed in 80°C hot water for 10 seconds is -10% or more and 10% or less in both the longitudinal and transverse directions. 5. A laminate comprising at least one layer of the polyester film according to any one of claims 1 to 4. 6. A packaging bag comprising at least a portion of the polyester film according to any one of claims 1 to 4 or the laminate according to claim 5. Effect of the Invention

[0008] The polyester film of the present invention has excellent aroma retention, high heat-cutting seal strength, and good resistance to tearing when used as a packaging bag and contains a liquid. Therefore, the polyester film of the present invention can provide a packaging bag that has excellent aroma retention, high heat-cutting seal strength, and can contain a liquid. [Brief description of the drawings]

[0009] [Figure 1] FIG. 4 is a diagram showing a method for measuring the impact strength of a melt-cut sealed portion.

[0010] The polyester film of the present invention is composed of a resin having at least an ester bond in the molecular main chain skeleton, and satisfies the following requirements (1) and (2): (1) The loss tangent (tan δ) obtained when measuring dynamic viscoelasticity at 25°C is 0.03 or more and 0.15 or less in the longitudinal direction. (2) When the film is welded and sealed in the width direction, the strength of the weld seal is 5N / 15mm or more and 20N / 15mm or less.

[0011] The polyester film of the present invention, which satisfies the above requirements, is difficult to adsorb various organic compounds and has excellent melt-cutting sealability. Therefore, when this film is used as a bag, even if food or the like is put in it, odor does not leak, making it suitable for packaging bags. Furthermore, packaging bags having the polyester film of the present invention have good resistance to tearing when liquid is put in the contents. Therefore, it can be carried with liquid in the contents. The polyester film of the present invention will be described below.

[0012] 1. Characteristics of polyester films Next, the properties required for the polyester film of the present invention will be described.

[0013] 1.1. Welding seal strength First, when the polyester film of the present invention is heat-sealed, the average seal strength must be 5N / 15mm or more and 20N / 15mm or less. If the heat-seal strength is less than 5N / 15mm, the heat-sealed portion is easily peeled off, and the bag is easily broken, so it cannot be used. The heat-seal strength is preferably 6N / 15mm or more, and more preferably 7N / 15mm or more. The higher the heat-seal strength, the better, but the upper limit currently available is about 20N / 15mm, and even 15N / 15mm can be said to be practically preferable. The heat-sealing method will be described in the examples below. 1.2.Impact strength of fusion-sealed parts The polyester film of the present invention is preferably melt-sealed so that the longitudinal direction is the tensile direction, and the impact strength measured by applying an impact ball of a film impact tester to the melt-sealed portion is preferably 0.4 J or more and 0.8 J or less. As a result of intensive research, the present inventors have found that when a bag containing a liquid is dropped, the liquid impacts the melt-sealed portion in a short time of 0.003 seconds. Since the impact strength measurement showed that the bag broke in a time close to that time, the impact strength measurement is a condition close to that of an actual dropped bag. If the impact strength of the melt-sealed portion is less than 0.4 J, the bag is vulnerable to instantaneous impact, and when the bag is dropped with a liquid contained in the content, the bag is likely to break, and therefore cannot be used. The impact strength of the melt-sealed portion is more preferably 0.45 J or more, and particularly preferably 0.5 J or more. On the other hand, if the impact strength of the melt-sealed portion exceeds 0.8, the loss tangent (tan δ) at 25°C described later exceeds 0.15, and there is a risk of the bag sticking to the roll or the aroma retention being deteriorated. The method for measuring the impact strength of the welded sealed portion will be described in the Examples.

[0014] 1.3. Glass transition temperature (Tg) The polyester film of the present invention preferably has a Tg of −75° C. or more and 25° C. or less. The Tg is more preferably −70° C. or more and 20° C. or less, and particularly preferably −65° C. or more and 15° C. or less. The Tg and impact strength will be explained with reference to Non-Patent Document 1.

[0015] Fig. 2 in Non-Patent Document 1 shows the temperature dependence of the Tg of rubber and the Charpy impact strength of ABS resin. Fig. 2 shows that when the temperature at which the impact strength is measured is equal to or lower than the Tg of rubber, the impact strength increases. On the other hand, it is shown that when the temperature at which the impact strength is measured is higher than the Tg of rubber, the impact strength increases. In other words, it is considered that the impact strength is high when the Tg is equal to or lower than the measurement temperature. In light of this concept, since room temperature is usually around 25°C, by setting the Tg to 25°C or lower, the resistance of the bag to break when liquid is added to the contents at room temperature is improved. On the other hand, when the Tg is lower than -75°C, the loss tangent (tan δ) at 25°C described later exceeds 0.15, the viscosity increases, and there is a risk that the film will stick to the roll during film formation or processing, or that the aroma retention will be poor.

[0016] 1. Loss tangent (tan δ) at 4.25°C The polyester film of the present invention must have a tan δ of 0.03 or more and 0.15 or less at 25°C in the longitudinal or transverse direction. Tan δ is expressed as E'' (loss modulus) / E' (storage modulus), where E'' indicates the viscosity term and E' indicates the elasticity term. At Tg or higher, the polymer is devitrified, exhibits high viscosity, and the value of tan δ is large. If tan δ at 25°C is less than 0.03, E' indicating the elasticity term will have a high value, and when a bag containing a liquid in the contents is dropped at room temperature, the impact strength of the above-mentioned melt-sealed part will decrease, and the bag will break without being able to absorb the impact. Tan δ at 25°C is preferably 0.04 or more, more preferably 0.05 or more. On the other hand, if tan δ exceeds 0.15, the viscosity will increase and there is a risk of adhesion to the roll. If tan δ exceeds 0.15, there is a risk of increased amorphousness, a smaller apparent specific gravity as described below, and poor aroma retention. It is sufficient that tan δ is within the above range in either the longitudinal direction or the width direction, but it is preferable that tan δ is within the above range in both the longitudinal direction and the width direction. The method for measuring tan δ will be described in the Examples.

[0017] 1.5.Folding angle The polyester film of the present invention preferably has a folding angle of 20 degrees or more and 80 degrees or less, as measured by the method described below. When the opening of a bag using a film with a folding angle of 80 degrees or less is twisted, the twist is maintained and the bag can be sealed without tying the opening. If the folding angle is 80 degrees or more, the bottom of the bag is difficult to crease and the bag bulges, so that the edges of the bags are not uniform when stacked. The upper limit of the preferred folding angle is 75 degrees, and it is more preferable if the upper limit is 70 degrees. In addition, the smaller the folding angle, the more preferable it is, but the lower limit of the range that can be covered by the present invention is 20 degrees, and even if the folding angle is 25 degrees or more, it can be said that it is practically preferable.

[0018] 1.6.Shrinkage ratio The polyester film of the present invention preferably has a hot water heat shrinkage rate of −10% or more and 10% or less in both the longitudinal and transverse directions when immersed in 80° C. hot water for 10 seconds. If the hot water shrinkage rate exceeds 10% in both the longitudinal and transverse directions, the film will shrink significantly in a high-temperature environment, making it difficult to maintain its original shape. In particular, if the hot water shrinkage rate is large in the transverse direction, there will be a large variation in the strength of the heat-cut seal. When the film is cut, it is melted by the heat from the cutting blade, and is immediately cooled and solidified to form a mass of resin (a so-called seal ball). If the film has heat shrinkability in the transverse direction, the film will shrink due to the heat from the cutting blade, causing variation in the size of the seal ball formed after cutting, resulting in variation in the strength of the heat-cut seal.

[0019] The hot water heat shrinkage rate is preferably 9% or less, more preferably 8% or less, and even more preferably 7% or less in both the longitudinal and transverse directions. On the other hand, if the hot water heat shrinkage rate is below 0%, it means that the film stretches, and if the film stretches greatly, the film tends to have difficulty maintaining its original shape, as in the case of a high shrinkage rate. Therefore, the hot water shrinkage rates in the longitudinal and transverse directions are preferably -9% or more, more preferably -8% or more, and even more preferably -7% or more. The hot water heat shrinkage rates in the longitudinal and transverse directions do not need to be the same, and the hot water heat shrinkage rates in the longitudinal and transverse directions may be different as long as they are within the above range of the hot water heat shrinkage rate.

[0020] 1.7. Variation in strength of heat-sealed parts The standard deviation of the weld seal strength when the polyester films of the present invention are laminated and weld-sealed is preferably 0.3 to 2.5. The method of determining the standard deviation of the weld seal strength will be described in the examples below. If the standard deviation of the weld seal strength is higher than 2.5, the variation in the weld seal strength will be large. If the variation in the weld seal strength is large, even if the average value of the weld seal strength of the entire bag exceeds 5N / 15mm, there will be many parts where the weld seal strength is below 5N / 15mm when viewed partially, and the bag will be easily torn from those parts, making it difficult to use as a packaging bag. The smaller the standard deviation of the weld seal strength, the less the variation in the weld seal strength, so it is preferable, but at the current technical level, 0.3 is the lower limit. The standard deviation of the weld seal strength is preferably 2 or less, more preferably 1.5 or less, and even more preferably 1 or less. Furthermore, even if the lower limit of the standard deviation of the heat-seal strength is about 0.4 or 0.5, the bag can be used as a packaging bag without any problems.

[0021] 1.8. Apparent Specific Gravity The polyester film of the present invention has an apparent specific gravity of 1.0 g / cm 3 More than 1.4g / cm 3 The apparent specific gravity is preferably 1.02 g / cm or less. 3 More than 1.38g / cm 3 More preferably, it is 1.04 g / cm or less. 3 More than 1.36g / cm 3 It is particularly preferable that the apparent specific gravity is 1.0 g / cm or less. 3 If the apparent density is less than 1.4g / cm, the crystallinity will be low and the aroma retention may be poor, whereas if the apparent density is more than 1.4g / cm, the material will be difficult to melt when heated and the melt-cutting and sealing strength may be reduced.

[0022] 1.9.Thickness The thickness of the polyester film of the present invention is not particularly limited, but is preferably 3 μm or more and 200 μm or less. If the thickness of the film is less than 3 μm, there is a risk of insufficient strength and difficulty in processing such as printing. The film may be thicker than 200 μm, but the film will require more heat during welding and sealing, resulting in poor welding and sealing properties. In addition, if the thickness is greater than 200 μm, the weight of the film used will increase, leading to higher manufacturing costs, which is not preferable. The thickness of the film is more preferably 5 μm or more and 160 μm or less, and even more preferably 7 μm or more and 120 μm or less.

[0023] 2. Polyester film constituent materials 2.1. Types of polyester raw materials The polyester resin used in the present invention is a resin having at least an ester bond in the molecular main chain.

[0024] In addition, the polyester resin used in the present invention preferably uses 30 mol% to 70 mol% of a saturated polycarboxylic acid component as a monomer that can lower the glass transition temperature (Tg) and increase the value of the loss tangent (tan δ) at room temperature described below. More preferably, it is 35 mol% to 65 mol%. If the saturated polycarboxylic acid component is more than 70%, there is a risk of adhesion to the roll and deterioration of the aroma retention. On the other hand, if the saturated polycarboxylic acid component is less than 30 mol%, the glass transition temperature becomes high, the loss sine (tan δ) at room temperature described below and the impact strength of the sealed part decrease, and there is a risk of the bag breaking when dropped as a packaging bag with liquid in the contents.

[0025] Examples of saturated polycarboxylic acids include aliphatic dicarboxylic acids such as adipic acid, azelaic acid, sebacic acid, and decanedicarboxylic acid, and alicyclic dicarboxylic acids such as 1,4-cyclohexanedicarboxylic acid.

[0026] Among the above-mentioned saturated polycarboxylic acids, adipic acid and azelaic acid are preferred. By using one or more of these, the Tg of the film can be set to 25° C. or less, and the tan δ at 25° C. can be easily set to 0.03 or more.

[0027] The polyester resin used in the present invention preferably contains 30 mol % or more and 70 mol % or less of an unsaturated polycarboxylic acid. Examples of the unsaturated polycarboxylic acid include aromatic polycarboxylic acids, such as terephthalic acid, isophthalic acid, orthophthalic acid, and aromatic dicarboxylic acids such as naphthalenedicarboxylic acid.

[0028] Among the above unsaturated polycarboxylic acids, terephthalic acid, isophthalic acid, and orthophthalic acid are preferred, and terephthalic acid and isophthalic acid are more preferred. By using one or more of these, good aroma retention can be achieved.

[0029] As the polyhydric alcohol component constituting the polyester resin used in the present invention, ethylene glycol is used, and in addition, an aliphatic diol component that lowers Tg more than ethylene glycol is preferably used in an amount of 30 mol % or more, more preferably 45 mol % or more.

[0030] Examples of the aliphatic diol component include long-chain diols such as diethylene glycol, 1,3-propanediol, 2,2-diethyl-1,3-propanediol, and 1,4-butanediol, and aliphatic diols such as hexanediol.

[0031] Among these, diethylene glycol, 1,3-propanediol, and 1,4-butanediol are preferred because they have the effect of improving the above-mentioned tan δ. By using one or more of these, the Tg of the film can be made 25° C. or less, and the tan δ at 25° C. can be made 0.03 or more.

[0032] Furthermore, polyester elastomers containing ε-caprolactone, tetramethylene glycol, etc. may be used as components constituting the polyester-based resin. Polyester elastomers are preferably used because they have the effect of lowering the glass transition temperature (Tg) of the film. Polyesters such as polylactic acid, including polyesters containing aliphatic hydroxycarboxylic acid components such as lactic acid, also have the effect of lowering the Tg of the film, but they may reduce the mechanical strength, so it is preferable not to include them.

[0033] 2.2.Other Ingredients In the resin constituting the polyester film of the present invention, various additives such as waxes, antioxidants, antistatic agents, crystal nucleating agents, viscosity reducing agents, heat stabilizers, coloring pigments, coloring inhibitors, ultraviolet absorbers, etc. can be added as necessary. In addition, fine particles may be added as a lubricant to improve the slipperiness of the film. As the fine particles, any fine particles can be used. For example, inorganic fine particles can include silica, alumina, titanium dioxide, calcium carbonate, kaolin, barium sulfate, etc., and organic fine particles can include acrylic resin particles, melamine resin particles, silicone resin particles, crosslinked polystyrene particles, etc. The average particle size of the fine particles can be appropriately selected as necessary within the range of 0.05 μm to 3.0 μm (measured by a Coulter counter). In addition, the amount of fine particles added is within the range of 200 to 1200 ppm in the film, and good slipperiness (friction) and transparency can be achieved at the same time.

[0034] The method of blending the above-mentioned fine particles in the resin constituting the polyester film is not particularly limited, and for example, a method of adding at any stage of producing polyester resin can be mentioned.As the stage of adding fine particles, for example, it is preferable to add the fine particles as a slurry dispersed in ethylene glycol or the like at the stage after the completion of esterification reaction or before the start of polycondensation reaction, and proceed with polycondensation reaction.In addition, a method of blending a slurry of fine particles dispersed in ethylene glycol, water, or other solvent with polyester resin raw material using a vented kneading extruder, or a method of blending dried fine particles with polyester resin raw material using a kneading extruder can also be mentioned.

[0035] 2.3.Layer configuration The layer structure may be a single layer (B layer), two kinds of two layers (B layer / A layer), two kinds of three layers (A layer / B layer / A layer), etc., but a layer structure of two or more layers is preferable, and two kinds of three layers is particularly preferable. In the B layer, it is preferable to use 30 mol% to 70 mol% of a saturated polyvalent carboxylic acid component as a monomer that can lower the glass transition temperature (Tg) and increase the value of the loss tangent (tan δ) at room temperature described later. By using a monomer that can lower the Tg as described above in the B layer, it is possible to improve the resistance to bag breakage when the bag is dropped with the contents containing a liquid. On the other hand, if the monomer that can lower the Tg is used, the viscosity increases and there is a risk of adhesion to the roll, so it is preferable to use a polyester-based resin that contains ethylene terephthalate as the main component (i.e., contains 50 mol% or more) as shown in the A layer of the example. In the A layer, it is preferable to contain one or more monomer components that can become amorphous components in a total amount of 12 mol% to 30 mol% as a monomer that can reduce the folding retention angle. If the total amount of monomer components that can be amorphous components exceeds 30 mol%, the tear resistance and heat resistance tend to be insufficient, which is not preferable. Examples of monomers that can be amorphous components include neopentyl glycol, 1,4-cyclohexanedimethanol, and isophthalic acid. Among these, it is particularly preferable to use neopentyl glycol.

[0036] The layer ratio of layer B in the laminated film is preferably 50% or more. If the layer ratio of layer A is less than 50%, the loss tangent (tan δ) value at room temperature described below decreases, and a packaging bag melt-sealed using the film has reduced resistance to rupture when the bag is dropped with liquid inside, which is not preferable. In the case of a single-layer structure, the film may be a single-layer film consisting of layer B made of the above-mentioned polyester resin.

[0037] 3. Polyester film production conditions 3.1.Melt extrusion The polyester film of the present invention can be obtained by melt-extruding the polyester raw material described above in "1. Polyester raw materials constituting the polyester film" using an extruder to form an unstretched film, and then subjecting the unstretched film to a predetermined method described below. The film may be unstretched, or may be stretched by any stretching method, such as uniaxial stretching or biaxial stretching, but from the viewpoint of film strength and productivity, a film obtained by biaxial stretching is preferable. The polyester resin is obtained by selecting the type and amount of a dicarboxylic acid component and a diol component and polycondensing them. In addition, a chip-shaped polyester resin obtained in advance by polycondensation can be used alone or in combination of two or more types as a raw material for the film.

[0038] When the raw resin is melt-extruded, it is preferable to dry the polyester raw material using a dryer such as a hopper dryer or a paddle dryer, or a vacuum dryer. After drying the polyester raw material in this way, it is melted at a temperature of melting point + 60°C to melting point + 100°C using an extruder and extruded as a film. Any existing method such as a T-die method or a tubular method can be used for extrusion.

[0039] Thereafter, the film melted by extrusion is quenched to obtain an unstretched film. As a method for quenching the molten resin, a method can be suitably adopted in which the molten resin is cast from a die onto a rotating drum and quenched and solidified to obtain a substantially unoriented resin sheet. The film is preferably stretched in at least one direction, either the longitudinal (length) direction or the transverse (width) direction (uniaxially stretched film, biaxially stretched film). In the following, a sequential biaxial stretching method by transverse stretching-longitudinal stretching in which transverse stretching is performed first and then longitudinal stretching is performed will be described, but the reverse order of longitudinal stretching-transverse stretching may also be used since only the main orientation direction is changed. A simultaneous biaxial stretching method may also be used.

[0040] 3.2. Lateral stretching The unstretched film obtained by quenching after melt extrusion is stretched in the transverse direction in a tenter (first tenter) with both ends in the width direction of the film held by clips. The conditions for transverse stretching are preferably Tg to Tg+30°C and a ratio of about 3 to 5 times. In the case of lamination, the temperature is set based on the layer with the higher Tg. If the stretching temperature is lower than Tg, the film is likely to break not only in the transverse stretching but also in the longitudinal stretching in the subsequent process, since the oriented crystallization of the film due to the transverse stretching is promoted. On the other hand, if the transverse stretching temperature is higher than Tg+30°C, there is a risk that the thickness unevenness in the width direction will exceed 18%. It is preferable to perform preheating prior to transverse stretching, and the preheating should be performed until the film surface temperature reaches Tg to Tg+30°C.

[0041] Furthermore, if the transverse stretching ratio is less than 3 times, not only will the thickness unevenness in the width direction easily exceed 18%, but there is also a risk of breakage occurring in the final heat treatment step described below. If the transverse stretching ratio is less than 3 times, the stretching is less likely to propagate to the end of the film (the edge of the clip), and there is a risk of a large amount of unstretched portions (so-called stretch residue) in the film edge portions. Since the molecules of the film edge portions where the stretch residue occurs are not oriented compared to the center of the film and the elastic modulus is significantly lower, the thermal shrinkage stress in the width direction occurring in the final heat treatment step is concentrated near the stretch residue. As a result, the thickness (resin volume) near the stretch residue moves toward the center of the film in the width direction, and as a result, the thickness of the film edge portions in the width direction is rapidly reduced, and the strength is weakened, resulting in breakage.

[0042] After the transverse stretching, it is preferable to pass the film through an intermediate zone where no active heating operation is performed. If there is a temperature difference between the transverse stretching zone and the intermediate heat treatment zone of the first tenter, the heat (hot air itself or radiant heat) from the intermediate heat treatment zone may flow into the transverse stretching process, causing the temperature in the transverse stretching zone to become unstable, and the film quality may become unstable. Therefore, it is preferable to pass the film after the transverse stretching and before the intermediate heat treatment for a predetermined time through the intermediate zone and then supply it to the intermediate heat treatment zone. In this intermediate zone, if the hot air from the transverse stretching zone or the intermediate heat treatment zone is blocked so that a strip of paper is hung down in the vertical direction almost completely when the film has not passed through it, a film of stable quality can be obtained. The passing time through the intermediate zone is sufficient for about 1 to 5 seconds. If it is shorter than 1 second, the length of the intermediate zone is insufficient, and the effect of blocking the hot air is insufficient. In addition, it is preferable to pass the intermediate zone for a longer time, but if it is too long, the equipment will become large, so about 5 seconds is sufficient.

[0043] After passing through the intermediate zone, intermediate heat treatment is performed before longitudinal stretching. This intermediate heat treatment can reduce the shrinkage in the width direction. The temperature of the intermediate heat treatment is preferably in the range of the same as the transverse stretching temperature to +30°C. If the temperature of the intermediate heat treatment zone is lower than the transverse stretching temperature, it is difficult to achieve the effect of reducing the transverse shrinkage. On the other hand, if it is higher than the transverse stretching temperature +30°C, the shrinkage in the width direction is lower, but the film may be crystallized too much, making it difficult to perform the subsequent longitudinal stretching. The passing time of the intermediate heat treatment zone is preferably 2 to 20 seconds. If it is shorter than 2 seconds, the length of the intermediate heat treatment zone may be insufficient, making it difficult to adjust the heat shrinkage in the width direction. The passing time of the intermediate heat treatment zone is preferably longer, but about 20 seconds is sufficient. This results in a transverse uniaxially stretched film.

[0044] During the intermediate heat treatment, a relaxation treatment can also be performed by shortening the distance between the clips of the first tenter by any desired factor. The relaxation treatment relaxes the molecules oriented in the transverse direction without crystallizing, and the shrinkage rate in the width direction can be reduced. The relaxation after the transverse stretching can be set arbitrarily within the range of 0% (a relaxation rate of 0% means that no relaxation is performed) to 20%. If the relaxation rate is higher than 20%, the orientation of the end portion (the edge portion of the film) is relaxed too much, decreasing the elastic modulus, and there is a risk of breakage in the final heat treatment step as described above.

[0045] 3.3. Longitudinal stretching Then, the film is stretched longitudinally. In the longitudinal stretching process, the uniaxially stretched film is first introduced into a longitudinal stretching machine in which a plurality of roll groups are arranged in series. In the longitudinal stretching, it is preferable to preheat the film with a preheating roll until the film temperature reaches Tg to Tg+30°C. In the case of lamination, the film temperature is set based on the layer with the highest Tg. If the temperature is lower than Tg, it tends to be difficult to stretch in the longitudinal direction (i.e., breakage is likely to occur). On the other hand, if the temperature is higher than Tg+30°C, the film is likely to stick to the roll, and there is a risk of roll contamination occurring early in continuous production. When the film temperature reaches the above range, longitudinal stretching is performed. The longitudinal stretching is performed by the speed difference of the rolls. The stretching ratio is preferably 1.5 to 5 times. In addition, the number of stretching stages can be increased to two-stage stretching, which uses two rolls, low speed and high speed, two-stage stretching, which uses three rolls, low speed, medium speed, and high speed, and three-stage stretching, which uses four rolls, low speed, medium-low speed, medium-high speed, and high speed. Any of rolls, near infrared rays, far infrared rays, hot air heaters, etc. can be used as the heating means. In addition, the relaxation in the longitudinal direction can be performed not only immediately after the longitudinal stretching, but also by narrowing the clip interval in the longitudinal direction in the final heat treatment as described later. Conditions such as temperature and relaxation rate will be described later. After relaxation in the machine direction (longitudinal stretching when relaxation is not performed), the film is preferably cooled once, preferably with a cooling roll having a surface temperature of 20°C to 40°C.

[0046] Next, the film after longitudinal stretching and cooling is introduced into a second tenter, where it is subjected to a final heat treatment and a simultaneous relaxation treatment. Since the longitudinal and transverse shrinkage rates can be adjusted in the final heat treatment, it is a preferred embodiment to carry out the final heat treatment step after the film is stretched. The relaxation in the second tenter can be carried out at any magnification in both the longitudinal and transverse directions. The relaxation rate in both the longitudinal and transverse directions is preferably 0% to 50%. The lower limit of the relaxation rate is 0%. If the relaxation rate is too high, there is a disadvantage that the production speed and product width of the film are reduced, so the upper limit of the relaxation rate is preferably about 50%.

[0047] The heat treatment (relaxation treatment) temperature is preferably 100°C to 200°C. If the heat treatment temperature is lower than 120°C, it is difficult to make the shrinkage rate of the film 10% or less. On the other hand, the higher the heat treatment temperature, the lower the shrinkage rate of the film, which is preferable. However, if the heat treatment temperature is higher than 160°C, as described above, the thickness of the film at the end in the width direction is reduced, which may cause breakage. Furthermore, if the final heat treatment temperature is higher than 160°C, there is a risk that the film will stick to the inside of the tenter when it comes into contact with the film. After the final heat treatment, both ends of the film are cut and removed while being wound up to obtain a polyester film roll.

[0048] The polyester film obtained as described above may be subjected to a surface treatment step to impart various properties to the film surface before or after being wound into a film roll. Examples of such surface treatment include corona treatment and flame treatment for improving the adhesiveness of the film surface, and coating treatment for imparting antistatic properties. These treatments can improve the adhesiveness and antistatic properties.

[0049] 4. Laminates and packaging bags using polyester films The polyester film of the present invention can be used alone, or can be laminated with other materials to form a laminate. The laminate only needs to have at least one layer of the polyester film of the present invention, and this gives the laminate the above-mentioned properties such as the heat-sealing strength.

[0050] Examples of other layers constituting the laminate include, but are not limited to, unstretched films containing polyethylene terephthalate as a constituent component, unstretched, uniaxially or biaxially oriented films containing other amorphous polyesters as a constituent component, unstretched, uniaxially or biaxially oriented films containing nylon as a constituent component, and unstretched, uniaxially or biaxially oriented films containing polypropylene as a constituent component.

[0051] Although there are no particular limitations on the position of the polyester film in the laminate, it is preferable that the polyester film of the present invention is present as the outermost layer of the laminate, which allows the laminate to exhibit excellent heat-cutting and sealing performance. The method for producing the laminate is not particularly limited, and any conventionally known method for producing a laminate, such as a coating method, a co-extrusion method, a lamination method, or a heat sealing method, can be used.

[0052] The polyester-based film and laminate having the above-mentioned characteristics can be suitably used as a packaging bag. The entire packaging bag may be made of the polyester-based film or laminate according to the present invention, but it is sufficient that the above-mentioned polyester-based film or laminate is present in at least a part of the packaging bag. For example, by providing the above-mentioned polyester-based film in the heat-sealed portion of the packaging bag, the packaging bag has excellent heat-sealing properties, and the occurrence of waviness in the heat-sealed portion can be prevented. Furthermore, when the packaging bag is made of the above-mentioned polyester-based film or laminate, in addition to having excellent heat-sealing properties, the packaging bag has excellent aroma retention and good resistance to tearing when liquid is added to the contents.

[0053] There is no particular limitation on the method for providing a polyester film or laminate in a portion of the packaging bag, and methods similar to those for producing laminates, such as coating, lamination, and heat sealing, can be used.

[0054] Packaging bags are generally made by heat-cutting and sealing, but are not limited thereto, and conventionally known manufacturing methods such as heat-sealing using a heat bar (heat jaw), adhesion using hot melt, center sealing using a solvent, etc. Since the polyester film of the present invention has excellent heat-cutting and sealing performance, a packaging bag having a beautiful appearance can be obtained even when made by heat-cutting and sealing.

[0055] The packaging bag of the present invention can be suitably used as a packaging material for various items such as food, medicines, and industrial products. EXAMPLES

[0056] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the following examples, and it is possible to carry out the present invention by making appropriate modifications within the scope of the above and below-mentioned aims, and all of these modifications are included in the technical scope of the present invention.

[0057] <Film evaluation method> [Average value and variation of welding seal strength] The film was folded in half so that the crease was along the film flow direction, and set in a welding machine (Kyoei Printing Machinery Materials Co., Ltd., PP500 type side welder), and the film was welded and sealed under the conditions of a welding blade angle of 90 degrees, a blade tip temperature of 410°C, and a shot rate of 140 bags / min to produce a side-sealed bag. The size of the bag was 310 mm in the direction along the welding seal line (width direction of the film roll) x 220 mm in the direction perpendicular to the welding seal line (flow direction of the film roll) (hereinafter, unless otherwise specified, the direction along the welding seal line will be referred to as the "width direction" and the direction perpendicular to that will be referred to as the "flow direction"). One bag was randomly taken from the prepared bag, and a total of 40 samples (20 on each side) measuring 15 mm in width and 100 mm in flow direction were sampled from the heat-sealed portion (310 mm on each side x 2 = 620 mm on both sides). In accordance with JIS Z1707, the sample was opened 180 degrees and both ends were set in a universal tensile tester (Shimadzu Corporation, Autograph AG-X plus) (chuck distance: 50 mm), and a tensile test was performed in the longitudinal direction (flow direction) of the sample at a speed of 200 mm / min to measure the peel strength when the heat-sealed portion broke. The maximum peel strength was recorded as the heat-seal strength per 15 mm (N / 15 mm), and the average value of the 40 samples was taken as the average heat-seal strength. The standard deviation calculated using the following formula 1 was used as the variation in the heat-cutting seal strength. Standard deviation =[{(X1-X0) 2 +(X2-X0) 2 +···+(X n -X0) 2} / n] 1 / 2 formula 1 X n : Welding seal strength of the nth sample X0: Average value of melt-cutting seal strength n: Number of samples (40)

[0058] [Folding holding angle] The film pieces were left in a thermostatic chamber at 20°C and 65% RH for 24 hours. Immediately afterwards, each film was cut into a 10cm x 10cm square in a 20°C and 65% RH environment and folded in four (5cm x 5cm square). When folding the film, the short side of the rectangle formed by the first 2 folds was in the flow direction. The film folded in four was then sandwiched between two pieces of glass measuring 10cm x 15cm and 2mm thick, and a 5kg weight was placed on the glass and pressed for 10 seconds. The weight was removed from the film folded in four, and the film was left for 10 seconds, after which the angle at which the film opened was measured with the last crease as the base point. The angle when the film was completely folded was 0 degrees, and the angle when the film was completely opened was 180 degrees. In the case of a two-layer structure, the measurement was made with layer B folded in a valley.

[0059] [Loss tangent (tan δ) at 25℃] A sample measuring 10 mm in width direction x 40 mm in flow direction was cut out according to a procedure compliant with JIS-K7244, and heated from -150°C to 150°C at a heating rate of 10°C / min, a frequency of 1Hz, and a chuck distance of 20mm using a dynamic viscoelasticity device (Hitachi, Ltd., DMA7100). The value of tan δ at 25°C was obtained from the tan δ curve obtained at that time.

[0060] [Impact strength measurement of welded seal parts] Samples with the average welded seal strength were taken out, and a film impact tester (B-121402302, manufactured by Toyo Seiki Seisakusho Co., Ltd.) was used to measure impact strength. As shown in Figure 1, a total of three samples were taken, each measuring 100 mm in width direction x 100 mm in flow direction, with the welded sealed part in the center. The film was fixed with a jig with the welded sealed side facing down and the welded sealed part perpendicular to the equipment. The impact strength was measured when the welded sealed part broke by hitting it with a hammer from the welded sealed side, as shown in Figure 1. A 2J hammer was used to impact the test pieces.

[0061] [Falling Bag Rating] Bags were prepared in the same manner as in the measurement of the heat-seal strength. Four bags were randomly selected from the bags, 100 mL of water was poured into the bags, and the tops were tied to prepare samples for the drop bag evaluation. The bottom of the sample (opposite the opening) was dropped from a height of 50 cm toward the floor 10 times, and the number of times until the bag broke was calculated as the drop bag score, as shown below. The drop bag score was calculated as the sum of the scores after four trials (maximum 10 points x 4 trials = 40 points, minimum 1 point x 4 trials = 4 points). Bag breaks on first try: 1 point Second attempt: 2 points 3rd attempt: 3 points 4th attempt breaks the bag: 4 points 5th attempt breaks the bag: 5 points 6th attempt breaks the bag: 6 points 7th attempt breaks the bag: 7 points 8th attempt breaks the bag: 8 points 9th attempt breaks the bag: 9 points No broken bags: 10 points A drop bag score of 20 points or more was considered a pass (○), and a score of 19 points or less was considered a fail (×).

[0062] [Fragrance retention] Two pieces of film cut into a 10 cm x 10 cm square were stacked together, and an impulse sealer (Hakko Corporation, No. 310-1) was used to melt-seal three sides at 250°C to create a three-sided sealed bag with only one side open. 20 g each of limonene (Nacalai Tesque, Inc.) and menthol (Nacalai Tesque, Inc.) were placed in the bag, and the open side was also melt-sealed to seal the bag. The limonene used was dissolved in ethanol to a concentration of 0.05 wt%. The menthol used was dissolved in ethanol to a concentration of 1 g / mL. The bag was placed in a 1000 mL glass container and the lid was placed on it. One day later, people (a total of 16 people, aged 4 in their 20s, 4 in their 30s, 4 in their 40s, and 4 in their 50s; the ratio of men to women in each age group was half and half) opened the lid of the glass container so that they could smell the air inside, and then smelled the air in the glass container and made a judgment as follows. A sample was rated as passing (○) if the number of people who detected the odor was 5 or less, and as failing (×) if 6 or more people detected the odor.

[0063] [Apparent specific gravity] The mass of the film cut into a 10 cm x 10 cm square was measured. The thickness of the sample was measured, and the apparent specific gravity was calculated using the following formula 2.

[0064]

number

[0065] [Hot water heat shrinkage rate] The film was cut into a 10 cm x 10 cm square and immersed in warm water at 80°C ± 0.5°C for 10 seconds without load to allow it to shrink, then immersed in water at 25°C ± 0.5°C for 10 seconds and removed from the water. The dimensions of the film in the width direction and machine direction were then measured, and the shrinkage rate in each direction was calculated according to the following formula 3. The measurement was performed twice and the average value was calculated. Shrinkage rate (%) = {(length before shrinkage - length after shrinkage) / length before shrinkage} x 100 Formula 3

[0066] [Tg (glass transition temperature)] Using a differential scanning calorimeter (DSC250, manufactured by TA Instruments) connected to an electric cooling system (RCS120), 2 mg ± 0.2 mg of film was heated from -120 ° C. to 150 ° C. in heat-only mode with temperature modulation, at a modulation period of 40 sec and 2 ° C. / min, and the reverse heat flow was obtained. The glass transition temperature (Tg) was determined as the temperature on the low-temperature side of the intersection between the extension line of the baseline below the glass transition temperature and the tangent line showing the maximum slope at the transition part. In Comparative Example 3, the glass transition temperature could not be observed in this range, so it could not be measured. <Preparation of polyester raw materials> [Synthesis Example 1] In a stainless steel autoclave equipped with a stirrer, a thermometer, and a partial reflux condenser, 100 mol % of dimethyl terephthalate (DMT) as a dicarboxylic acid component and 100 mol % of ethylene glycol (EG) as a polyhydric alcohol component were charged so that the molar ratio of ethylene glycol was 2.2 times that of dimethyl terephthalate, and 0.05 mol % (relative to the acid component) of zinc acetate was used as an ester exchange catalyst to carry out an ester exchange reaction while distilling off the produced methanol outside the system. Then, 0.225 mol % (relative to the acid component) of antimony trioxide was added as a polycondensation catalyst, and a polycondensation reaction was carried out at 280°C under reduced pressure of 26.7 Pa to obtain a polyester (A) with an intrinsic viscosity of 0.75 dl / g. This polyester (A) is polyethylene terephthalate.

[0067] [Synthesis Example 2] Using the same procedure as in Synthesis Example 1, polyesters (B) to (D) were obtained by changing the monomers. Polyester E is Ecofrex manufactured by BASF. The composition of each polyester is shown in Table 1. In Table 1, A A is adipic acid, BD is 1,4-butanediol, NPG is neopentyl glycol, and DEG is diethylene glycol. When producing polyester (D), SiO2 (Silysia 266 manufactured by Fuji Silysia Corporation) was added as a lubricant at a ratio of 7,000 ppm to the polyester. Each polyester was appropriately cut into chips. The intrinsic viscosities of polyesters B to D were B: 0.73 dl / g, C: 0.80 dl / g, and D: 0.75 dl / g, respectively. The number average molecular weight of polyester E was 44,000 g / mol. [Table 1]

[0068] [Example 1] Polyester A, polyester B, polyester C, and polyester D were mixed in a mass ratio of 25:60:10:5 to prepare a resin mixture for the skin layer. 100% polyester E was used for the core layer. Using two twin-screw extruders and a T-die mold equipped with a multi-manifold, the resins were co-extruded at a core layer temperature of 200°C and a skin layer temperature of 280°C, and then quickly cooled with a cooling roll to obtain an unstretched film with a thickness of 100 μm for the three layers of skin layer / core layer / skin layer. The unstretched film was introduced into a tenter (first tenter) that successively had a transverse stretching zone, an intermediate zone, and an intermediate heat treatment zone. In the intermediate zone, the hot air from the transverse stretching zone and the hot air from the intermediate heat treatment zone were blocked so that when a strip of paper was hung down without the film passing through it, the paper would hang down almost completely vertically. The unstretched film introduced into the first tenter was stretched laterally in the transverse stretching zone at 82°C and 3.8 times the original length. After passing through the intermediate zone (passing time = approximately 1.2 seconds), the film was introduced into the intermediate heat treatment zone and heat-treated at 97°C for 8 seconds while the clip width of the first tenter was reduced to perform 6% relaxation, thereby obtaining a transverse uniaxially stretched film. The transversely stretched film was introduced into a longitudinal stretching machine in which a group of rolls including low-speed and high-speed rolls were arranged in series, and the film was preheated on a preheating roll until the film temperature reached 90°C, and then stretched on low-speed and high-speed rolls to a stretch ratio of 2.8 times. Thereafter, the longitudinally stretched film was forcibly cooled by a cooling roll whose surface temperature was set to 25°C. The cooled film was then introduced into a tenter (second tenter) where it was heat-treated for 10 seconds in an atmosphere of 140°C while being relaxed by 17% in the lateral direction (film width direction) and then cooled. Both edges in the width direction were then cut and removed to obtain a polyester film with a thickness of approximately 13 μm. The production conditions and properties of the obtained film are shown in Tables 2 and 3.

[0069] [Example 2] Polyester films with different layer ratios were produced and evaluated. The film production conditions and properties of each example are shown in Tables 2 and 3.

[0070] [Example 3] Polyester A, polyester B, polyester C, and polyester D were mixed in a mass ratio of 25:60:10:5 to prepare a resin mixture for the skin layer. 100% polyester E was used for the core layer. Using two twin-screw extruders and a T-die mold equipped with a multi-manifold, the resins were co-extruded at a core layer temperature of 200°C and a skin layer temperature of 280°C, and then quickly cooled with a cooling roll to obtain an unstretched film with a thickness of 100 μm for the three layers of skin layer / core layer / skin layer. The unstretched film was fed to a simultaneous biaxial stretching tenter, and both ends were held by clips and simultaneously biaxially stretched to a longitudinal stretching ratio of 2 and a transverse stretching ratio of 3.8 at 95° C. Further, the film was heat-treated in a tenter oven at 150° C. for 10 seconds, and after cooling, both edges in the width direction were cut and removed to obtain a polyester film with a thickness of about 13 μm. The production conditions and properties of the obtained film are shown in Tables 2 and 3. [Examples 4 to 7] Polyester films with various layer configurations and layer ratios of the skin layer and core layer were produced and evaluated. In Examples 5 to 7, a matte cooling roll was used to obtain the unstretched film. When the two-kind, two-layer (A / B) film was heat-sealed, the B side was the inner side. The film production conditions and properties of each Example are shown in Tables 2 and 3.

[0071] [Comparative Example 1] Polyester A, polyester B, polyester D, and polyester E were mixed in a mass ratio of 25:60:10:5, fed into a twin-screw extruder, melt-mixed at 270°C, extruded through a T-die, and then cooled on a chill roll set at a surface temperature of 30°C to obtain an unstretched film. The unstretched film was introduced into a tenter (first tenter) that successively had a transverse stretching zone, an intermediate zone, and an intermediate heat treatment zone. In the intermediate zone, the hot air from the transverse stretching zone and the hot air from the intermediate heat treatment zone were blocked so that when a strip of paper was hung down without the film passing through it, the paper would hang down almost completely vertically. The unstretched film introduced into the first tenter was stretched laterally in the transverse stretching zone at 82°C and 3.8 times the original length. After passing through the intermediate zone (passing time = approximately 1.2 seconds), the film was introduced into the intermediate heat treatment zone and heat-treated at 97°C for 8 seconds while the clip width of the first tenter was reduced to perform 6% relaxation, thereby obtaining a transverse uniaxially stretched film. The transversely stretched film was introduced into a longitudinal stretching machine in which a group of rolls including low-speed and high-speed rolls were arranged in series, and the film was preheated on a preheating roll until the film temperature reached 90°C, and then stretched on low-speed and high-speed rolls to a stretch ratio of 2.8 times. Thereafter, the longitudinally stretched film was forcibly cooled by a cooling roll whose surface temperature was set to 25°C. The cooled film was then introduced into a tenter (second tenter) where it was heat-treated for 10 seconds in an atmosphere of 140°C while being relaxed by 17% in the lateral direction (film width direction) and then cooled. Both edges in the width direction were then cut and removed to obtain a polyester film with a thickness of approximately 13 μm. The production conditions and properties of the obtained film are shown in Tables 2 and 3.

[0072] [Comparative Example 2] Polyester A and polyester D were mixed in a mass ratio of 95:5, fed into a twin-screw extruder, melt-mixed at 270°C, extruded through a T-die, and then cooled on a chill roll with a surface temperature set at 30°C to obtain an unstretched film. This unstretched film was introduced into a tenter (first tenter) that successively had a transverse stretching zone, an intermediate zone, and an intermediate heat treatment zone. In the intermediate zone, the hot air from the transverse stretching zone and the hot air from the intermediate heat treatment zone were blocked so that when a rectangular piece of paper was hung down without the film passing through it, the piece of paper would hang down almost completely vertically. The unstretched film introduced into the first tenter was stretched transversely at 90°C and 3.8 times in the transverse stretching zone, passed through the intermediate zone (passing time = about 1.2 seconds), and then introduced into the intermediate heat treatment zone, where it was heat-treated at a temperature of 97°C for 8 seconds to obtain a transverse uniaxially stretched film. Note that no relaxation in the width direction was performed during the intermediate heat treatment. The transversely stretched film was then introduced into a longitudinal stretching machine in which a group of rolls including low-speed and high-speed rolls were arranged in series, and the film was preheated on a preheating roll until the film temperature reached 100°C, after which it was stretched on low-speed and high-speed rolls to a stretch ratio of 2.8 times. Thereafter, the longitudinally stretched film was forcibly cooled by a cooling roll whose surface temperature was set to 25°C. The cooled film was then introduced into a tenter (second tenter) where it was heat-treated for 10 seconds in an atmosphere of 230°C (relaxation rate in the film width direction: 0%), after which it was cooled and both edges were cut and removed to obtain a polyester film with a thickness of approximately 13 μm. The production conditions and properties of the obtained film are shown in Tables 2 and 3.

[0073] [Comparative Example 3] A non-stretched film having a thickness of 30 μm (Toyobo Co., Ltd., Rixfilm (L4103-30 μm)) was used and evaluated according to the above-mentioned method. The evaluation results are shown in Table 3.

[0074] [Comparative Example 4] A biaxially oriented polypropylene film having a thickness of 15 μm (manufactured by Toyobo, Pylen Film-FG (P5562-15 μm)) was used and evaluated according to the above-mentioned method. The evaluation results are shown in Table 3.

[0075] [Table 2]

[0076] [Table 3]

[0077] As shown in Table 3, the films of the examples were excellent in terms of resistance to bag rupture, aroma retention, and heat-sealing performance. In contrast, the film of Comparative Example 1 received a score of 8 points for bag drop. This result shows that the bag formed from the film of Comparative Example 1 is prone to breakage when dropped, and is therefore undesirable as a packaging bag. The film of Comparative Example 2 could not be processed into a bag by welding and sealing, so the strength of the welding and sealing, the impact strength of the welding and sealing, and the aroma retention could not be measured. The film of Comparative Example 2 could not be used as a bag. In addition, the step-like signal was unclear in the DSC measurement, so the Tg could not be measured.

[0078] The film of Comparative Example 3 had a high folding angle of 150 degrees, and the film opened up even after folding. Therefore, when the film was made into a bag, the crease at the bottom was not neat, and the appearance was inferior to the bags using the films of the Examples. The bag using the film of Comparative Example 3 also had poor aroma retention. The drop score of the film of Comparative Example 4 was 5 points. From this result, it can be seen that the bag formed from the film of Comparative Example 4 is prone to tearing when dropped, and is not suitable as a packaging bag. In addition, the folding angle was high at 180 degrees, and the film opened even after folding. Therefore, when made into a bag, the crease at the bottom was not neat, and the appearance was inferior to the bags using the films of the Examples. [Industrial Applicability]

[0079] INDUSTRIAL APPLICABILITY The polyester-based film of the present invention has aroma retention properties for various organic compounds, high heat-seal strength, and good resistance to tearing when used as a packaging bag to contain a liquid, making it suitable for use in packaging bags.

Claims

1. A single-layer or multi-layer stretched polyester film, which satisfies the following requirements (1) to (3) and has a layer containing, as a polycarboxylic acid component, 30 mol % or more and 70 mol % or less of one or more selected from the group consisting of adipic acid, azelaic acid, sebacic acid, and decanedicarboxylic acid. (1) The loss tangent (tan δ) obtained when dynamic viscoelasticity is measured at 25° C. is 0.03 or more and 0.15 or less in the longitudinal direction. (2) When the film is welded and sealed in the width direction, the strength of the weld seal is 5N / 15mm or more and 20N / 15mm or less. (3) Tg obtained by temperature modulated DSC measurement is -75°C or higher and -25°C or lower

2. 2. The polyester-based stretched film according to claim 1, wherein the folding angle is 20 degrees or more and 80 degrees or less.

3. A polyester-based stretched film as described in claim 1 or 2, characterized in that the thermal shrinkage rate when immersed in 80°C hot water for 10 seconds is between -10% and 10% in both the longitudinal and transverse directions.

4. A laminate comprising at least the polyester-based stretched film according to any one of claims 1 to 3.

5. A packaging bag comprising, at least in a part thereof, the stretched polyester film according to any one of claims 1 to 3 or the laminate according to claim 4.

Citation Information

Patent Citations

  • JP1973067857A

  • Resin composition, and film using the same

    JP2007262370A

  • Shaped articles from cycloaliphatic polyester compositions

    JP2007517926A

  • Polyester film and packaging bag using the same

    JP2017210541A